Prosthetic rehabilitation in a patient with an anophthalmic socket following enucleation for absolute glaucoma - Lisda Damayanti; Daisy Wulansari; Alyssa Salsabila (Indonesia Prosthodontic Association, 2025)
Absolute glaucoma is a progressive condition that causes irreversible optic nerve damage from elevated intraocular pressure. When it no longer responds to treatment, patients may develop severe pain and complete vision loss, making enucleation the final option for relief. After enucleation, prosthetic rehabilitation is essential to restore facial appearance, improve function, and support psychological well-being. This case report outlines the clinical course and prosthetic management of an anophthalmic socket after enucleation for absolute glaucoma, highlighting key fabrication steps and the importance of structured follow-up care. A 23-year-old male with worsening, treatment-resistant glaucoma experienced persistent pain, scleral redness, and complete vision loss, leading to enucleation in 2018. His first prosthesis loosened after two years, and recurrent socket bleeding in 2023 necessitated an additional surgery. A new custom prosthesis was fabricated using a polyvinyl siloxane impression, followed by wax try-ins and precise iris–pupil positioning with callipers and a PD ruler. Acrylic painting was applied to create a natural ocular appearance. After insertion, the prosthesis was evaluated for comfort, stability, and esthetics, with follow-ups at one day, one week, and six months. This case highlights the value of personalized prosthetic design and consistent aftercare in achieving optimal outcomes for patients with anophthalmic sockets.